Analisis Vegetasi Gulma pada Lahan Budidaya Kakao Menghasilkan di Kecamatan Payakumbuh, Lima Puluh Kota, Sumatera Barat - Friskia Hanatul Qolby; Fefriyanti DS; Sulastri Sulastri (Mahesa Research Institute, 2025)
One of the superior plantation commodities is cocoa (Theobroma cacao L.), which plays a role in absorbing labor, providing industrial raw materials and a source of foreign exchange. Cocoa is grow almost in all regions of Indonesia, in the global market Indonesia is first producer cocoa in Asia and the third in the world. To maintain and increase cocoa production, optimal handling is needed in all aspects including the agronomic aspect. One of the obstacles in the agronomic aspect is the presence of weeds which cause competition with cocoa in obtaining nutrients, water, sun, and growing space. If weeds are not controlled, they can cause growth disturbances and decreased production. Weed control must be carried out correctly and precisely. The first step in controlling weeds is vegetation analysis to find out the weeds that grow in the cocoa fields, then control techniques are determined. After analyzing the vegetation of weeds, it was found that there were 6 species of weeds that grew dominantly in the cocoa fields, namely, the dominant weeds in order were Paspalum conjugatum (SDR 34.70%), Borreria alata (SDR 24.30%), Persicaria odorata (SDR 18.20%), Imperata cylindrica (SDR 14.00%), Cyperus rotundus (SDR 5.60%), Ageratum conyzoides (SDR 3.20%).